Increasing The Capacity of Midwives in Implementing Monitoring and Education About Weight Gain Based on Pre Pregnancy BMI Status in Mempawah District, West Kalimantan Provience - Sulistiawati, Rini; Damayanti, Dini Fitri; Fajrin, Dessy Hidayati (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2023)
Monitoring pregnant women's weight gain based on pre-pregnancy Body Mass Index (BMI) can assist health workers in making appropriate clinical decisions and educational interventions about diet and physical activity of pregnant women. The results showed that specific weight gain education for pregnant women based on pre-pregnancy BMI status was effective on the suitability of increasing pregnant women's weight, so interventions to increase midwifery knowledge were needed in an effort to increase the ideal weight of pregnant women. The Pontianak Ministry of Health Polytechnic conducts community service every year in realizing the tridarma of higher education, one of which is through "Increasing the Capacity of Midwives in the Implementation of Monitoring and Education on Weight Based on Pre-Pregnant BMI Status in Mempawah District". The activity was carried out in the form of training with the target of 17 midwives in the working area of the Jungkat Health Center, Mempawah Regency. Activities carried out include preparation, implementation, and evaluation. The output target is in the form of increasing knowledge in understanding and being able to determine appropriate actions in monitoring and educating about weight based on pre-pregnancy BMI status. The results of the activities have been well organized. There are differences in the knowledge of midwives before and after being given training. There is a change in the behavior of midwives as indicated by filling in the weight gain chart according to pre-pregnancy BMI in the MCH book and providing appropriate education so that there is an increase in pregnant women's weight according to pre-pregnancy BMI status.